Analisis Kualitas Pelayanan dengan Metode Servqual dan AHP pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Muaro Jambi - Hetty Rohayani.AH, ST, M.Kom; Afrizal J, S.Kom (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
This research was doing to determine the service quality indicators. Where an indicator of qualityof service is a priority for improved by using a servqual method that includes five dimensions : Tangibles,Reliability, Responsivenes, Assurance and Emphathy and methods Analitytic Hierarchy Process.Is population information system service quality in the Department of Population and CivilRegistration Muaro Jambi regency was in a state of good, and the criteria which services are still needed.Based on the analysis results with servqual method, all the indicators in the assessment ofservice quality should be improved, in light of the AHP weighting obtained Empathy indicators that havethe highest level of service quality, while Tangibles is the highest indicator of quality of service should beimproved.Key Word : the service quality, servqual, AHP method